1998
DOI: 10.1597/1545-1569(1998)035<0447:stfpio>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Salvaging the Failed Pharyngoplasty: Intervention Outcome

Abstract: Rates of primary pharyngeal flap failure are roughly equivalent to rates of primary sphincter pharyngoplasty failure. Pharyngeal flap and sphincter pharyngoplasty failures can be salvaged with revisional surgery, which can provide a velopharyngeal mechanism capable of complete closure. Revisional surgery is usually associated with denasal speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Surgical procedures include the enlargement of the posterior pharyngeal wall with various injectable materials, the lengthening of the palate by pushback palatoplasty and pharyngeal flap, sphincter pharyngoplasty or pharyngeal flap alone [10,11]. Pharyngeal flaps can be based superiorly, inferiorly, or laterally [12,13]. Indications for surgery must take into account the social impact of the child's speech and the age of the child because the recovery period is quite uncomfortable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical procedures include the enlargement of the posterior pharyngeal wall with various injectable materials, the lengthening of the palate by pushback palatoplasty and pharyngeal flap, sphincter pharyngoplasty or pharyngeal flap alone [10,11]. Pharyngeal flaps can be based superiorly, inferiorly, or laterally [12,13]. Indications for surgery must take into account the social impact of the child's speech and the age of the child because the recovery period is quite uncomfortable.…”
mentioning
confidence: 99%
“…In the 3 sPRS who underwent pharyngeal surgery, results were also very satisfactory with postoperative scores of 1, 1/2, and 2. Witt et al [13] reported that over a 9-year period, about 15% of patients who underwent pharyngeal flap surgery or sphincter pharyngoplasty for velopharyngeal dysfunction required revision. Surgical failure can be the result of surgical error and/or inadequate lateral pharyngeal wall motion [22].…”
mentioning
confidence: 99%
“…Barot et al 3 reported similar results, while Witt et al 40 reported a slightly higher percentage (20%) of revisional surgery. Three causes can be identified for the unsatisfactory functional outcome with respect to nasal resonance.…”
Section: Discussionmentioning
confidence: 84%
“…Successful outcome with respect to nasal resonance of the sphincterpharyngoplasty ranged from 67% to 85% 26 . Both sphincterpharyngoplasty and pharyngeal flap operations require revisional surgery to treat unsatisfactory functional results in about 15-20% 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal flap is a surgical procedure widely applied in the VPI management. This method aims to create a partial mechanical nasopharyngeal obstruction, favoring velopharyngeal closure during the speech (9,10) . Thus, due to the pharyngeal patency reduction caused by the flap, some cases may exhibit respiratory changes resulting from the nasopharyngeal obstruction (11) .…”
Section: Introductionmentioning
confidence: 99%